2013
DOI: 10.1007/s10103-013-1284-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the laser and light-emitting diode (LED) phototherapy on midpalatal suture bone formation after rapid maxilla expansion: a Raman spectroscopy analysis

Abstract: The aim of this study was to analyze the effect of laser or light-emitting diode (LED) phototherapy on the bone formation at the midpalatal suture after rapid maxilla expansion. Twenty young adult male rats were divided into four groups with 8 days of experimental time: group 1, no treatment; group 2, expansion; group 3, expansion and laser irradiation; and group 4, expansion and LED irradiation. In groups 3 and 4, light irradiation was in the first, third, and fifth experimental days. In all groups, the expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Rate of bone resorption under a specific force is dependent on the degree of maturity and mineral content of the bone as immature bone is resorbed more quickly under compressive forces (53). Studies have shown that laser irradiated bony defects exhibit higher degree of maturity and more calcified foci in less time (54).…”
Section: Discussionmentioning
confidence: 99%
“…Rate of bone resorption under a specific force is dependent on the degree of maturity and mineral content of the bone as immature bone is resorbed more quickly under compressive forces (53). Studies have shown that laser irradiated bony defects exhibit higher degree of maturity and more calcified foci in less time (54).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, low-level laser therapy (LLLT) techniques have been applied to soft tissues 2 as a complement to other treatments, because it is a noninvasive technique that—with the application of low light energy—acts as a cellular “photo-modulator”, 1 , 8 stimulating cell proliferation, 9 bone healing, and regeneration. 3 , 5 , 8 , 10 , 11 …”
Section: B Ackgroundmentioning
confidence: 99%
“…Durante o período inicial de pesquisa da terapia fotodinâmica moderna, os fenotiazínicos têm sido um padrão de fotossensibilizador bioativo, dando um rendimento razoável de oxigênio singleto (forma do oxigênio mais reativo e oxidante que o oxigênio molecular) e absorvendo luz na janela terapêutica (definida pela faixa de frequência na qual a laserterapia é mais efetiva) para terapia fotodinâmica (de λ 600 nm a λ 900 nm), sendo, assim, um ponto inicial de síntese de novas moléculas 152 .…”
Section: Fotoquimioterapia Em Protozoáriosunclassified